2001
DOI: 10.1116/1.1398541
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural pressure sensor based on an enhanced resonant mode hysteresis effect

Abstract: Influence of cross-sectional geometry on the sensitivity and hysteresis of liquid-phase electronic pressure sensors Appl.A micromachined pressure sensor based on an array of microswitches Rev. Sci. Instrum. 81, 055103 (2010);Enhanced hysteresis effects are seen in the resonant behavior of a magnetically actuated oscillating microcantilever at large deflections. These effects, which are produced by resonant mode coupling, take the form of abrupt changes in the amplitude of oscillation. These changes in amplitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…These sensor structures are manufactured in metal-oxide-semiconductor ͑MOS͒ arrangements by micromachining technology methods. This is the hysteresis effect which Brown et al 16 found and used for precise pressure measurement in the vacuum range. In the following a magnetically stimulated CIC structure is presented as an example of this kind of pressure sensor.…”
Section: Miniaturized Friction Gaugesmentioning
confidence: 98%
See 1 more Smart Citation
“…These sensor structures are manufactured in metal-oxide-semiconductor ͑MOS͒ arrangements by micromachining technology methods. This is the hysteresis effect which Brown et al 16 found and used for precise pressure measurement in the vacuum range. In the following a magnetically stimulated CIC structure is presented as an example of this kind of pressure sensor.…”
Section: Miniaturized Friction Gaugesmentioning
confidence: 98%
“…Brown et al 16 suggested the structure shown in Fig. These sensor structures are manufactured in metal-oxide-semiconductor ͑MOS͒ arrangements by micromachining technology methods.…”
Section: Miniaturized Friction Gaugesmentioning
confidence: 99%
“…For our devices, g (x, y) is approximately equal to 75 pN µm −2 applied on the traces at the ends of each nested cantilever and zero elsewhere. Although we have observed non-linear hysteresis effects in the motion of our CICs [12,13], in this paper we are concerned only with the linear regime, where the cubic term, z 3 , may be neglected. Analysis of the non-linear equation (3.1) is given in [13] and will not be repeated here.…”
Section: Resonance Theorymentioning
confidence: 99%
“…Although we have observed non-linear hysteresis effects in the motion of our CICs [12,13], in this paper we are concerned only with the linear regime, where the cubic term, z 3 , may be neglected. Analysis of the non-linear equation (3.1) is given in [13] and will not be repeated here. Thus, for arbitrary ω dr , we consider only small deflections of the device where we can set k to zero in (3.1).…”
Section: Resonance Theorymentioning
confidence: 99%
“…Mikro-Piranis) [1,2] wurden in ju Èngster Zeit auch mikrostrukturierte Kapazita Èts-und Gasreibungsvakuummeter [3][4][5][6] [20] und REDHEAD [21] konnten zeigen, dass eine solche sog. Dabei wurden zahlreiche bekannte Messprinzipien in den verschiedensten mikrostrukturierten Druckwandlern erfolgreich umgesetzt.…”
Section: Introductionunclassified